Le agevolazioni fiscali dell'attività degli enti religiosi nel Terzo Settore: dal diritto speciale al regime comune (Società e diritti, 2024)
In this article the authors reconstruct the overall picture of the position of ecclesiastical institutions in the reform of the Third Sector, and analyse a series of tax benefits, with particular reference to those that affect the buildings intended for the exercise of institutional activities, according to methods of non-commercial use.